The Icebound Land - John Flanagan (London : Corgi Yearling, 2008)
Kidnapped after the fierce battle with Lord Morgarath, Will and Evanlyn are bound for Skandia as captives aboard a fearsome wolfship. But Halt has sworn to rescue them, and he will do anything to keep his promise - even defy his King. Expelled from the Rangers he has served so loyally, Halt is joined by Will's friend Horace as he travels towards Skandia. On their way, they face many challenges - but Horace knows a thing or two about combat. Soon he begins to attract the attention of knights and warlords for miles around with his uncanny skill. Even so, will they be in time to rescue Will from a horrific life of slavery?